Evaluación de los riesgos químicos por hexano, heptano y octano y su incidencia en la salud de los trabajadores del área de despachos del terminal de productos limpios Ambato de EP PETROECUADOR: Propuesta diseño de cabinas con extractores de gases. - Urbina Pombosa, Medardo Hermenegildo (2016)
For the current research topic general objective assess chemical risks hexane, heptane and octane in an effort to prove the hypothesis under the following parameters: Chemical hazards hexane, heptane and octane affect the health of workers terminal area offices Ambato clean products of EP Petroecuador. Research methods were used hypothetical - deductive according to specific objectives. the dispatch areas Terminal Products Clean Ambato at high risk chemical hexane, heptane and octane thus resulting in a dose of 1,68 which it is a dangerous dose health: With the applied methods such as results found workers in addition to this the survey where most respondents stress that if they suffer discomfort in his health from exposure to chemicals such as hexane, heptane and octane with what proved the hypothesis argues. From the results we found was raised design cabins gas extractors allowing performance tests and succeeded in reducing pollution by about 50%, value obtained through measurements made after built the cabins, which meant that the dose concentration of these chemicals (hexane, heptane and octane) are within the allowed limit TWA TLV.